Biologically Inspired Techniques in Many-Criteria Decision Making : International Conference on Biologically Inspired Techniques in Many-Criteria Decision Making (BITMDM-2019) /: International Conference on Biologically Inspired Techniques in Many-Criteria Decision Making (BITMDM-2019). (2020) - Unknown
No abstract available